ANALISIS INTENSITAS KEBISINGAN TERHADAP PERUBAHAN NILAI AMBANG DENGAR PEKERJA SEBELUM DAN SETELAH TERPAPAR KEBISINGAN DI UNIT RING FRAME SPINNING 5 PT APAC INTI CORPORA, BAWEN – SEMARANG - Ardanariswari Ardanariswari; Irawan Wisnu Wardana; Sri Sumiyati (Jurnal Teknik Lingkungan, 2013)
Sound in specific intensity which is caused by production engines in factories that operated for 24 hours all day are potentially causes one of  environment pollution impact, in this case is noise pollution. Main impact of noise are exposure objects surrounds the engines, that is Hearing Threshold Level (HTL) reduction of workers surrounds who are exposed by noise from that engines. This research is purpose to survey and analyze a noise intensity in Ring Frame area on Spinning 5 unit PT APAC INTI CORPORA, Bawen-Semarang and to analyze the diferrence of workers’re HTL before and after exposed by noise in that area. Before is when first time the workers work  in that area, and after is when this research did. Based on worker’re audiometric tests did in June 12th, 2013 for 15 workers in that area, shown that Hearing Threshold Level average of 4 workers suffered minor deaf right ear. And 3 workers suffered minor deaf left ear. The comparation result of hearing threshold level before and after exposed by noise in that area, can be inferred that occurs the increasing of Hearing Threshold Level (hearing reduction) of workers in that area. From comparative statistic analysis test Paired Sample T-Test, signification value (probability) is 0,000 < 0,05 that H0 denied (H1 accepted). So can be conclude that there is a strong relation between differences of Hearing Threshold Level before and after exposed by noise in that area.